TINJAUAN YURIDIS PERAN DINAS LINGKUNGAN HIDUP DALAM PENANGANAN SAMPAH DI WILAYAH PESISIR PANTAI KOTA PAREPARE - Muthmainnah, Nurhaedah Hasan, Vina Wulandari Mursjid (Madani Legal Review, 2021)
The purpose of this study is to find out the juridical review of the role of the environmental service in handling waste in the coastal area of ​​Parepare City, and to find out the constraints of the environmental service in handling waste in the coastal area of ​​Parepare City. This study uses a descriptive-qualitative type of research with an empirical normative approach. The data collection techniques used are by means of library research, field studies and interviews. Based on this research, it shows that in carrying out its role the Environmental Service regarding waste transportation has been equipped with facilities and infrastructure including garbage transportation cars or cars (fleets). So the regulation on the role of the Environment Agency in the waste reduction target from 2018 to 2021 has increased, while the waste handling target from 2018 to 2021 has gone up and down. As for the constraints of the Environmental Service in achieving its objectives, namely from the environmental analysis carried out, internal factors can be identified and external factors related to waste management in Parepare City.